2021
DOI: 10.15849/ijasca.211128.09
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Non-Performing Financing Using Logistic Regression and Synthetic Minority Over-sampling Technique-Nominal Continuous (SMOTE-NC)

Abstract: Financing analysis is the process of analyzing the ability of bank customers to pay installments to minimize the risk of a customer not paying installments, which is also called Non-Performing Financing (NPF). In 2020 the NPF ratio at one of the Islamic banks in Indonesia increased due to the decline in people’s income during the Covid-19 pandemic. This phenomenon has led to bad banking performance. In December 2020 the percentage of NPF was 17%. The imbalance between the number of good-financing and NPF custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In summary, SVM-SMOTE (Tang et al, 2009) was the best oversampling method in both datasets. Wongvorachan et al (2023) selected Random Oversampling, Random Undersampling, and a combination of SMOTE-NC (Nominal and Continuous) (Islahulhaq et al, 2021) and Random Undersampling to compare its improvements on the High School Longitudinal Study dataset. The study adopted Random Forest as the classifier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In summary, SVM-SMOTE (Tang et al, 2009) was the best oversampling method in both datasets. Wongvorachan et al (2023) selected Random Oversampling, Random Undersampling, and a combination of SMOTE-NC (Nominal and Continuous) (Islahulhaq et al, 2021) and Random Undersampling to compare its improvements on the High School Longitudinal Study dataset. The study adopted Random Forest as the classifier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address this class imbalance, we employed a hybrid resampling technique. Specifically, we implemented the Synthetic Minority Oversampling Technique for nominal and categorical data (SMOTE-NC) and random undersampling (RUS) to increase minority cases and decrease majority cases [62,63]. The SMOTE-NC algorithm synthesized 80% of the minority cases, while the RUS algorithm undersampled non-minority cases to match the number of minority cases.…”
Section: Dataset and Data Preprocessingmentioning
confidence: 99%
“…This study employs the synthetic minority oversampling technique-nominal continuous as suggested by Chawla et al [14] since it balances a dataset by handling continuous and categorical features simultaneously. SMOTE-NC is chosen over other data balancing techniques because it is simple, computationally efficient, and has exceptional performance as shown by different researchers such as Rahmayanti et al [25] and Islahulhaq and Ratih [26] in their studies. In addition, it's also worth mentioning that SMOTE-NC works with any classification approach since it is independent of the classifier.…”
Section: Synthetic Minority Oversampling Technique-nominal Continuous...mentioning
confidence: 99%
“…However, SMOTE-NC is intended for datasets with both categorical and numerical features; it's not well suited for datasets with categorical features only [14]. Islahulhaq and Ratih [26] notes that a dataset can be categorised as imbalanced if the cases of minority class are less than 35% of cases from the majority class, that is, if the imbalance ratio is less than 0.35.…”
Section: Synthetic Minority Oversampling Technique-nominal Continuous...mentioning
confidence: 99%
See 1 more Smart Citation